Drivers of emotions and purchase intention in virtual supermarket setting: explore the rule of mental imagery, product involvement and presence - Correia, Carolina Ferreira (2019)
In this competitive market, companies more and more pay attention on consumer satisfaction by giving a great experience. Many marketing tools have been used to create the right atmosphere during the shopping experience which should stimulate positive emotions to the individual and consequently influence the purchase intention. Virtual Reality is one of the tools that marketers have investigated to understand its benefits in consumers’ behaviour. Some researches have been made in this field but there is still a lot left to explore. In this vein, the presented dissertation intends to explore how a computer-generated supermarket can affect some factors, that are believed in literature can influence the purchase intention. In order to contribute to the existing literature, this study will analyse the effect of Mental Imagery, Product Involvement and Presence on customer’s emotions during a shopping experience and on the purchase intention. The model was tested in the laundry detergent category. Moreover, a moderator analyses was made to evaluate the effect of some variables inherent to this category’s consumers. A virtual scenario was created, and the participants experienced a supermarket with virtual reality. Findings reveal that a virtual atmosphere has impact in consumers experience. Mental imagery has the most significant impact on the emotions generated whereas presence has a strong influence on purchase decision. Oppositely, product involvement has any effect on emotions. In addition, the obsession for laundry products highly decrease the effect of product involvement on purchase intention.